The sustainability of agriculture as a development tool in Namibia - Hansen, Gregory Craig (Department of Environmental and Geographical Science, 2023)
In order to address the inequitable distribution of land and to initiate socio-economic development amongst marginalised people in Namibia, the Namibian Resettlement Programme was introduced as a means of implementing land reform. There is a political, economic and social necessity for empowerment amongst many communities, however, land redistribution will not necessarily achieve this in the Namibian environment. The cost of implementing this Resettlement Programme has been very high and the benefits accruing to the settlers have been limited. It is argued that a primary reason for the lack of success of the Programme is that its agricultural focus requires all settlers to become successful farmers in an exceedingly harsh natural and economic environment. The sustainability of using agriculture is as a development tool in Namibia is assessed using certain environmental sustainability criteria. These were biophysical, economic, social, and political sustainability. Based on these criteria it is evident that Namibia does not have a comparative advantage in agricultural production and therefore should not promote agriculture as a means to achieve development. While the agricultural sector is already a significant employer in Namibia, there is limited scope for expansion of the industry and intensification of production is not sustainable because of the dry climate and associated low carrying capacity of the land. There is a need for research into other sectors of the Namibian economy in which Namibia may have a greater comparative advantage and hence would be better placed to act as a basis for development programmes. The Namibian Government should be encouraging other forms of job creation, such as tourism, and providing support to entrepreneurs undertaking new enterprises in sectors of the economy where the people of Namibia can sustainably exploit a comparative advantage.